Թվանշային գրադարանների ստեղծման անհրաժեշտությունը - Հայրապետյան, Նելլի Ալիկի (Հայկական գրադարանային ասոցիացիա)
The study shows that libraries are structures where the printed materials that have come down to us are preserved to pass on to the next generation. To solve this problem, modern libraries use the opportunities provided by information technologies. Along with the traditional functions of libraries, electronic functions are being formed: electronic registration of the reader, electronic service, electronic search of material, etc. As a result, the quality of service to readers is greatly improved. The character of the librarian is changing. Librarians with knowledge of modern information technologies are required. This is a qualitative step towards the use of arti-ficial intelligence in libraries. The creation of digital libraries becomes necessary. They provide access to material at any time, from any place, and ensure long-term preservation of library collections. The use of open source systems is emphasized. Armenian libraries are actively digiti-zing, using open/free source software. A number of programs are already widely used in Arme-nian libraries, which makes it possible to carry out large-scale digitization works.
Keywords: Թվանշային գրադարաններ